Two Byzantine Medical Texts in Verse Translated into English: Diagnosis and Treatment of Disease - Bouras-Vallianatos, Petros (DELTOS, 2024)
This article aims to provide an English translation of two particularly popular Byzantine medical texts in verse, focusing on diagnosis by the examination of venesected blood and urine. Furthermore, these texts provide valuable therapeutic advice, especially for the use of drugs. They are composed in the form of liturgical hymns, combining mnemonic techniques. These hymns survive in various recensions and are often ascribed either to Nikephoros Blemmydes or Maximos Planoudes, both late Byzantine intellectuals and renowned teachers of advanced educational programs in Nicaea and Constantinople, respectively.